The Impact Of Bank Size On Pre-and Post-merger And Acquisition Performance And Stability: New Evidence From Gcc And Pakistan - Nazim Ullah; Fauzias Mat Nor; Junaidah Abu Seman; Nur Ainna Binti Ramli; Ahmad Fadly Nurullah Bin Rasedee (Logos University International, Florida, United State, 2024)
International Journal of Professional Business Review, Volume 8 Issue 11 Page (1-21)